A retrospective analysis of substance use among female psychiatric patients in Saudi Arabia - Alodhayani, Abdulaziz A.; Almutairi, Khalid M.; Vinluan, Jason M.; Alonazi, Wadi B.; Alzahrani, Hatim Gormallah; Batais, Mohammed Ali; Kaki, Fatmah Mohammed; Almigbal, Turky H.; Alsaad, Saad (Frontiers in Psychology, 2022)
Abstract Objective: This study investigated the prevalence of substances use, and its risk factors, among females attending psychiatric outpatients center in Saudi Arabia. Design: A retrospective cross-sectional design Methods: We reviewed outpatients’ records of 200 female patients from a psychiatric unit in Jeddah, Saudi Arabia from December 2018 until February 2019. The researchers developed the pro forma, and 2 psychiatrists and a family medicine physician validated the form. Results: The most common and widely used was psychoactive substances (58%), followed by CNS depressants (22%), and finally Cannabinols (9.5%). Overall, the highest substance use was the amphetamine-cannabis-nicotine (ACN) representing nearly half of the illicit items (46.6%), followed by heroine-alcohol-benzodiazepine (16.4%), and with the lowest being benzodiazepine-nicotine (1.7%). There was a significant difference between the single substance and multiple substance use in terms of age (p = 0.001), smoking behavior (p = 0.001), patients past history (p = 0.005) and age of the patient at start of drug use (p = 0.005). Conclusion: Although the prevalence of substance use among females is low in Saudi Arabia, the screening of substance use disorders risks and building a rehabilitation program to control drug dependence are needed.